Does CSR Limit Corporate Power Or Advance IT? - Paulson, Laurence (2009)
In recent years more attention has been focussed on the actions of corporations in society. This can be due to any number of reasons; a more active media, globalisation or dissatisfied stakeholders. Despite the reason behind this change in mindset corporations have found themselves victim to much more consumer attention and scrutiny regarding their actions. Corporate Social Responsibility (CSR) is seen as an answer to these concerns. Corporations often view CSR as a form of stakeholder management to better understand the issues raised by those most affected by their actions. Others see it as a recognition that corporations have far more responsibilities within society than just profit maximisation and growth. Essentially CSR is the bridge between the corporation and society. This dissertation examines the role of the corporation within society and attempts to explore how it reached its current position and it what capacity the corporation operates an inherently privileged position. It will also examine critiques of CSR to more accurately gauge how far CSR acts to limit corporate power or if it in fact advances it. The study found that the corporation’s position within society is in fact a privileged one and that this power is maintained through undemocratic means. It was also found that CSR does offer a variety of ways for corporate power to be negated, specifically through stakeholder empowerment, consumer sovereignty and pluralistic reconceptualisations of business-society interactions. However despite these theories, it was found that the corporation’s privileged position afforded it rights and powers that, although inherently undemocratic, enabled the corporation to capture the CSR agenda and commoditise it to its own advantage.